Model predictive control of an on-board fast battery charger for electric mobility applications - Pedrosa, Delfim Duarte Rolo (2017)
Under the necessities of reducing emissions and air pollution, and also for increasing fuel economy, automotive companies have been developing electric and plug-in hybrid electric vehicles. Since these vehicles are parked when the batteries are being charged, it is possible to use the traction power converter as on-board charger, also allowing to reduce weight, volume and costs of components in the vehicle. In this context, this paper presents a model predictive control algorithm for an on-board fast battery charging that uses the traction power converter of an electric vehicle. Simulation results and system implementation are depicted, and finally, are presented some experimental results obtained with the proposed control system.